Chemical Characteristics of Beef Rawon in Malang City (Faculty of Animal Science Universitas Brawijaya, 2021)
Malang city as a travel destination in East Java has various regional culinary such as rawon. Rawon was a dark soup made from beef broth, kluwak (Pangium edule) paste, sliced beef and various spices, served with rice and often topped with bean sprout. Spices are obtained from natural plants that have a strong aroma and are often used as food mixtures or preservatives. Different ingredients, cooking methods and the heating process will produce different quality of rawon. The quality of rawon in Malang city was still unknown. By knowing the quality of rawon in Malang, parts used in the manufacture of rawon include ribs, brisket, samcan meat and each rawon merchant shop uses a different type. Consumers can choose rawon with the best quality in terms of nutritional value. The purpose of this research was to know the pH, moisture content, fat content, total calories and fatty acid profile of rawon in Malang City. This research used a descriptive quantitative research method. Rawon samples were obtained from several districts in Malang city. The data were analyzed statistically using excel to get the standard deviation based on the method. The results showed that the quality of rawon in Malang city has a pH of 4.80 ± 0.22 to 6.31 ± 0.16, moisture content 44.07 ± 0.15 to 74.81 ± 0.16, fat content 9.86 ± 0.18 to 17.62 ± 0.19, total calories 88.38 ± 0.24 to 201.06 ± 0.14, rawon consists of 19 saturated fatty acids and 18 unsaturated fatty acids saturated. It can be concluded that rawon beef in Malang was a nutrient dense food and its nutritional content varies depending on the beef used, the recipe and the cooking process.